Teknik Maksimalisasi Keamanan Jaringan Hotspot Link dengan Metode Filtering IP Address dan MAC Address Pada SMA 1 Stabat - Vidya Fitrah Aura; Surya Ananda; Reni Aulia; Reni Safitri; Sumarlin; Devita Permata Sari (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Use of Hotspot services in daily life every year in increasing, because the Hotspot network makes it easy for its users. But besides the convenience, the Hotspot network also has weaknesses. Each user has the right to enter and exit easily into the network. This cause security holes to become vulnerable to access rights being breached. One way to secure the Hotspot Link network is by using the IP Address And MAC Address filtering method, it is able to drop the IP Address And MAC Address of each connected client. This research was conducted using Mikrotik, Radio HS AirPo and the Winbox Application. The result of this study are able to maintain and overcome security problems in the Hotspot network.